COMPARATIVE INVESTIGATION OF PALYNOLOGICAL CHARACTERS OF CUSCUTA REFLEXA AND FEW MEMEBERS OF CONVOLVULACEAE - Noshad; M. Ajaib; A. Kiran (Journal of Animal and Plant Sciences, 2020)
Cuscuta reflexa Roxb. belonging to family Cuscutaceae was explored for its pollen morphology and its pollen characters examined with light and scanning electron microscope were compared with six species belonging to family Convolvulaceae. Pollen samples were collected from Districts; Kotli, Bhimber and Mirpur, Azad Jammu & Kashmir, Pakistan. Flowers of Cuscuta reflexa Roxb., five species of Ipomoea including Ipomoea carnea Jacq.,Ipomoea cairica (L.) Sweet , Ipomoea hederacia Jacq., Ipomoea pes-tigridi sL., Ipomoea eriocarpa R.Br., Ipomoea arachnosperma Welw. and Convolvulus arvensis L. were collected. Pollen shape of these selected species are generally prolate, subprolate, prolate-spheroidal, oblate spheroidal and perpolate. The apertures of the pollens of these taxa were found scabrate, scabrate-perforate, reticulate and echinate-reticulate. Among the examined taxa, C. reflexa Roxb. has smallest size of pollen (2-5×2.5-5pm) while the largest pollen (28.5-37.6 x 24.7-28.9pm) belongs to the Ipomoe acarnea. It has been founded that pollen of Cuscuta reflexa Roxb. is prolate in shape and was similar to I. carnea Jacq, I. pes-tigridis L, I. eriocarpa R.Br pollens. Hierarchical cluster analysis based on pollens observations grouped I. arachnosperma and Cuscuta refelexa together at maximum similarity 99.86 at a distance level of 0.003. It has been concluded from this study that Cuscuta refelexa pollen are exactly similar to Ipomea arachnosperma on the bases of pollen morphology and exine appearance.
Keywords: Ipomea; Pollen; SEM; Cuscuta